2018
DOI: 10.1371/journal.pone.0204087
|View full text |Cite
|
Sign up to set email alerts
|

Self-learning of point-of-care cardiac ultrasound – Can medical students teach themselves?

Abstract: BackgroundPoint-of-care ultrasonography (PoCUS) is a rapidly evolving discipline that aims to train non-cardiologists, non-radiologists clinicians in performing bedside ultrasound to guide clinical decision. Training of PoCUS is challenging, time-consuming and requires large amount of resources. The objective of our study was to evaluate if this training process can be simplified by allowing medical students self-train themselves with a web-based cardiac ultrasound software.MethodsA prospective, single blinded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 23 publications
0
38
0
Order By: Relevance
“…Past studies have substantiated that the integration of CU curriculum in medical-school is feasible [ 7 11 ] and that medical students are capable of using this modality to achieve accurate results [ 5 , 7 , 8 , 12 , 13 ]. With a growing base of evidence in support of its utility, the demand for integration of CU training into the medical-school curriculum is on the rise.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have substantiated that the integration of CU curriculum in medical-school is feasible [ 7 11 ] and that medical students are capable of using this modality to achieve accurate results [ 5 , 7 , 8 , 12 , 13 ]. With a growing base of evidence in support of its utility, the demand for integration of CU training into the medical-school curriculum is on the rise.…”
Section: Introductionmentioning
confidence: 99%
“…This may not require much resources in terms of teachers. A recent study showed that lending students hand-held ultrasound devices for selfpractice and either providing them with e-learning or a practical course gave them equal abilities in conducting a short, structured ultrasound examination [21]. Handson self-training augmented by e-learning could be a preferable approach for teaching in future studies, but this approach was not evaluated in this study.…”
Section: Discussionmentioning
confidence: 96%
“…The literature has shown that instructors of various types and backgrounds, including trained senior medical students, nonclinical anatomists, and electronic programs, can effectively teach POCUS. 2,[26][27][28][29] Thus, it is possible for individuals to have learned POCUS and to teach it to medical students without having formal advanced training such as radiology residency or ultrasound fellowship. For example, residents learn basic skills in POCUS as part of routine training in EM and other disciplines.…”
Section: Limitationsmentioning
confidence: 99%